Analisis Sistem Web Commerce (WCM) Dalam Meningkatkan Profitabilitas Pada PT. Hamparan Anugerah Palembang - Nelly; Roy Saleh; Sri Sutandi; Lia Sari; Irsan (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
This study aims to determine the application of the Web Commerce (WCM) system in increasing profitability at PT. Hamparan Anugerah Palembang. The data used in this study are secondary data, The results showed that the profitability ratio of net profit margin (Net Profit Margin) in 2017 increased several times compared to the profitability period in several months in 2016,decreasing only 5 times, namely in April, June, July, September, and October. Meanwhile, the increase in Net Profit Margin profitability ratio occurred 7 times, namely in January, February, March, May, August, November, and December. Thus the use of the Web Commerce (WCM) system is quite efficient in increasing profitability at PT. Hamparan Anugerah Palembang.